The Effect of Naphthazarin on the Growth, Electrogenicity, Oxidative Stress, and Microtubule Array in Z. mays Coleoptile Cells Treated With IAA - Rudnicka, Małgorzata; Ludynia, Michał; Karcz, Waldemar (Frontiers in Plant Science, 2019)
Naphthazarin (5,8-dihydroxy-l,4-naphthoquinone, DHNQ) is a naturally occurring 1,4-naphthoquinone derivative. In this study, we focused on elucidating the toxic effect of this secondary metabolite on the growth of plant cells. The dose-response curves that were obtained for the effects of DHNQ on endogenous and IAA-induced growth in maize coleoptile segments differ in shape; in the first case, it is linear, while in the presence of auxin it is bell-shaped with the maximum at 1 µM. It was found that DHNQ at almost all concentrations studied, when added to the incubation medium inhibited endogenous growth (excluding naphthazarin at 0.001 µM) as well as growth in the presence of IAA. Simultaneous measurements of the growth and external medium pH of coleoptile segments indicated that DHNQ diminished or eliminated proton extrusion at all of the concentrations that were used. Interestingly, the oxidative stress in maize coleoptile cells, which was measured as hydrogen peroxide (H2O2) production, catalase activity, redox activity and malondialdehyde (MDA) content, increased at the lower concentrations of DHNQ (<1 µM), thus suggesting a specific character of its action. It was also found that naphthazarin at concentration higher than 0.1 µM caused the depolarisation of the membrane potential (Em). An analysis of the organisation and anisotropy of the cortical microtubules showed that naphthazarin at all of the concentrations that were studied changed the IAA-induced transverse microtubule reorientation to an oblique reorientation. Our results indicate that naphthazarin diminished the growth of maize coleoptile cells by a broad spectrum of its toxic effects, thereby suggesting that naphthazarin might be a hypothetical component of new bioherbicides and biopesticides.